2015
DOI: 10.2503/hortj.mi-058
|View full text |Cite
|
Sign up to set email alerts
|

Ionomic Analysis of Horticultural Plants Reveals Tissue-specific Element Accumulation

Abstract: Ionomic analysis was performed in three diverse fruit crops in order to characterize element concentrations in edible parts and to compare element concentrations between edible parts and vegetative organs and between species. Nineteen elements, including elements essential for human health, toxic elements, and elements with radioisotopes from nuclear reactors, were analyzed in apple (Malus domestica), Japanese pear (Pyrus pyrifolia), eggplant (Solanum melongena), and edamame (Glycine max). The concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Several important studies have demonstrated its utility. Ionomic analysis has been used to compare element concentrations between species and between plant organs of horticultural crops, including apple and Japanese pear (e.g., Shibuya et al, 2015). Ionomic analysis has become important for determining the authenticity of a wine's origin.…”
Section: ) Ionomic Analysis (Simultaneous Multi-element Analysis)mentioning
confidence: 99%
“…Several important studies have demonstrated its utility. Ionomic analysis has been used to compare element concentrations between species and between plant organs of horticultural crops, including apple and Japanese pear (e.g., Shibuya et al, 2015). Ionomic analysis has become important for determining the authenticity of a wine's origin.…”
Section: ) Ionomic Analysis (Simultaneous Multi-element Analysis)mentioning
confidence: 99%
“…Co and V significantly accumulated in fruits in RDFR than in WHFR ( Figure 7 ). Mo was the only element in which the ratio of fruits to leaves was a positive value ( Figure S2 ), whereas eggplant, which belongs to the same family of tomato, showed a negative ratio of fruits to leaves in the Mo concentration [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A coexpression analysis by RNA-seq indicated expression patterns of several transcription factors relevant to genes involved in the biosynthesis of ascorbic acid, carotenoids, and flavonoids [ 27 ]. Ionomic analysis indicated the similarity in element concentrations across species by classifying the element profiles in leaves and other organs [ 28 ]. In the past years, most studies have only used one high-throughput method to analyze horticultural crops.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the quality of vegetables and fruits, sugars [ 1 , 2 ], functional ingredients [ 3 ], and minerals [ 4 ] related to flavor and nutrition are important. Furthermore, texture is one of the most important criteria to evaluate quality.…”
Section: Introductionmentioning
confidence: 99%